A Cross-National Study of COVID-19 Impact and Future Possibilities Among Emerging Adults: The Mediating Role of Intolerance of Uncertainty. Issue 5 (October 2021) - Lanz, Margherita; Sorgente, Angela; Vosylis, Rimantas; Fonseca, Gabriela; Lep, Žan; Li, Lijun; Zupančič, Maja; Crespo, Carla; Relvas, Ana Paula; Serido, Joyce
The present research examined the association of perceived impact of COVID-19 on emerging adults' perceptions of their future and the potential mediating role of intolerance of uncertainty on these associations. Specifically, we investigated the associations of perceived financial impact, needed resource impact, and psychological impact on perceptions of future life and financial future. Using online survey data from emerging adults ( N = 1768) living in six countries (China, Italy, Lithuania, Portugal, Slovenia, and USA), we found that the perceived dimension of impact (i.e., finances, needed resources, and psychological) was negatively associated with perceptions of future life and financial future, despite mean level differences by country. The ability to tolerate uncertainty was a significant mediator only for psychological impact. We conclude the article with suggestions for applying our findings in the design of future interventions.